2022
DOI: 10.1016/j.jsxm.2022.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pelvic Floor Muscle Training on Sexual Dysfunction, Sexual Satisfaction of Partners, Urinary Symptoms, and Pelvic Floor Muscle Strength in Women with Overactive Bladder: A Randomized Controlled Study

Abstract: Background In women with overactive bladder (OAB), sexual dysfunctions and sexual satisfaction of their partners have been problems that are as important as urinary symptoms. Aim To investigate the effects of pelvic floor muscle training (PFMT) on sexual dysfunction, sexual satisfaction of partners, urinary symptoms, and pelvic floor muscle strength (PFMS) in women with OAB. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The first-line behavioral therapy includes bladder training and pelvic floor muscle training ( 5 ). Seyda Toprak Celenay et al found that pelvic floor muscle training could improve sexual dysfunction, sexual satisfaction of partners, urinary symptoms, and pelvic floor muscle strength in women with overactive bladder ( 6 ). If behavioral therapy does not work, oral antimuscarinics and mirabegron are recommended as second-line treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The first-line behavioral therapy includes bladder training and pelvic floor muscle training ( 5 ). Seyda Toprak Celenay et al found that pelvic floor muscle training could improve sexual dysfunction, sexual satisfaction of partners, urinary symptoms, and pelvic floor muscle strength in women with overactive bladder ( 6 ). If behavioral therapy does not work, oral antimuscarinics and mirabegron are recommended as second-line treatment.…”
Section: Introductionmentioning
confidence: 99%